HabitApp: New Play Technologies in Pediatric Cancer to Improve the Psychosocial State of Patients and Caregivers - Carrion-Plaza, Alicia; Jaen, Javier; Montoya-Castilla, Inmaculada (Frontiers in Psychology, 2020)
Childhood cancer involves long periods of hospitalization that trigger emotions such as fear or sadness. Previous research has studied the positive effects of technology games on improving the hospitalization experience, but most do not focus on caregivers and none allow interaction with the real time observation of a zoo. The present study evaluates the impact of HabitApp and assesses the short-term impact on the psychosocial state of patients and caregivers in order to improve the hospitalization experience. The participants in this study were 39 patients plus 39 caregivers. An observational scale and a set of self-reporting tests were used. A quantitative analysis by ANOVA revealed the significant main effect of play time, suggesting an improvement in patient’s and caregiver’s psychosocial factors from the pre-play period to ten minutes of play time. The evaluation of the psychological state showed a significant interaction effect between the patient’s affection rating factor and the patient’s psychological conditions, sadness, depression, and the caregiver’s somatic complaints, and between the patient’s satisfaction rating factor and the caregiver's psychological conditions, happiness and wellbeing. The qualitative analysis showed positive changes in the physical state, social interaction, hospital routines and emotional state, while the patients and caregivers’ satisfaction with HabitApp was high. These results confirm that it is important to continue studying this type of technology in order to develop better interventions to be included in an integral approach to this pathology considering caregivers into pediatric oncology patients’ play therapy.